Efek Mediasi Kepuasan Pada Faktor Yang Mempengaruhi Loyalitas Nasabah - Andriyani, Febria; Alimuddin Rizal (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Positive values ​​from customers regarding the product as well as the company are a form of customer satisfaction with the company, the customer does not stop until the product purchase process but also evaluates the product such as the benefits obtained to compare products. If the customer is satisfied, then there will be an incentive to choose and reuse the same product. However, if what happens is disappointment, the customer will quit or go to a competitor. The purpose of the study is to determine, test, and analyze the effect of corporate image on customer value, customer satisfaction on customer loyalty Based on the results of the study, it was found that there is a positive influence of the corporate image variable on customer satisfaction, there is a positive influence of the customer value variable on customer satisfaction, there is a positive influence of the corporate image variable on customer loyalty, there is a positive influence of the customer value variable on customer loyalty, there is The positive influence of the satisfaction variable on customer loyalty, satisfaction mediates the effect of corporate image on loyalty, satisfaction mediates the effect of customer value on loyalty.